FINANCIAL SUPPORT IN AGRICULTURE DURING PANDEMIC IN REPUBLIC OF NORTH MACEDONIA - Katerina Hadzi Naumova-Mihajlovska, Neda Petroska-Angelovska, Marija Takovska (Institute of Economic Sciences, 2023)
The agriculture sector in North Macedonia during pandemic was strongly influenced by market restrictions, lack of seasonal workers, restriction of movement, difficulties in the organization of transport and logistics. On the other hand, it shows greater resilience compared to other economic segments during the restrictions introduced at the beginning of the COVID-19 pandemic. The economic downturn, however, exacerbated the financial vulnerability of smallholder farms, drastically reducing available sources of income and employment. While the sources of financing in agriculture in North Macedonia are already poor, the global pandemic impact would result in the sort of collapse for the current trend. Thus, this paper focuses on how the impact of pandemic can be turned into an opportunity to boost agriculture financing to make the sector more resilient to it. Main purpose of the paper is to analyses the impact of restrictions introduced during COVID-19 pandemic and the implemented measures regarding the financial support in agricultural sector in North Macedonia in the period. Therefore, the methodology of research is based on qualitative and quantitative analyses of agricultural financing based on official data. Analyses show that the measures to mitigate the effects of a pandemic are short-lasting and inadequately designed for agriculture. Therefore, it’s important the need for a multidimensional approach and financial instruments to reinforce resilience in the agricultural sector. That means: facilitating access to financing sources, expanding their scope, and especially important is the strategic approach in financing the production of agricultural crops that are crucial in crisis conditions, such as the pandemic and the war in Ukraine.
European Economies after Covid-19: Challenges and Implications for the Macroeconomic Policy
Keywords: Agriculture development, financial support, pandemic crises